In vitro digestion of dairy and egg products enriched with grape extracts: Effect of the food matrix on polyphenol bioaccessibility and antioxidant activity. (October 2016) - Pineda-Vadillo, Carlos; Nau, Françoise; Dubiard, Catherine Guerin; Cheynier, Véronique; Meudec, Emmanuelle; Sanz-Buenhombre, Marisa; Guadarrama, Alberto; Tóth, Tamás; Csavajda, Éva; Hingyi, Hajnalka; Karakaya, Sibel; Sibakov, Juhani; et al.
Abstract: The aim of this study was to evaluate the effect of the food matrix on polyphenol bioaccessibility and antioxidant activity during the in-vitro digestion of dairy and egg products enriched with grape extracts (GE). Four GE-enriched matrices produced under industrial conditions (custard dessert, milkshake, pancake and omelet) and the GE dissolved in water (control solution) were submitted to in vitro digestion and the bioaccessibility of the major classes of polyphenols as well as the evolution of the antioxidant activity of the matrices were monitored at oral, gastric and intestinal level. Apart from the digestion effect itself, the release, stability and solubility of polyphenols was governed by mainly two factors: 1 — the composition and structure of the food matrices and 2 — the class of polyphenol. Results showed that the inclusion of the GE extracts into the different egg and dairy food matrices greatly impacted the release and solubility of anthocyanins and proanthocyanidins during digestion, especially in the solid food matrices and during the oral and gastric phases of digestion. Also, the presence of the food matrices protected anthocyanins from degradation during the intestinal phase. However, if the total phenolic content is considered at the end of the whole digestion process, the proportion of soluble (bioaccessible) and insoluble phenolics delivered by the enriched-matrices was quite similar to that of the control solution. On the contrary, the food matrix effect did not affect the antioxidant activity of the matrices, which remained constant during the oral and gastric phases but greatly increased during the intestinal phase of digestion. Among the GE-enriched matrices, omelet presented higher recoveries of total phenolics and antioxidant activity at the end of digestion. Highlights: In vitro polyphenol bioaccessibility depends on the food matrix in which it is embedded Food matrices protect anthocyanins from degradation during intestinal phase Inclusion in food matrices increases in vitro anthocyanin and proanthocyanidin bioaccessibility in most matrices Antioxidant capacity of the enriched matrices is not affected by the presence of the food matrices At the end of digestion, the enriched matrices deliver similar proportions of phenolic compounds than the control